PBL education plan for video content production class based on generative AI technology - Baek, Jiseon (Edelweiss Applied Science and Technology, 2025)
With the rapid advancement of digital technology, Generative AI has emerged as a transformative force in commercial advertising production, fundamentally reshaping traditional production methods. It enhances both productivity and creativity throughout the entire advertising process by supporting various stages such as scenario writing, image and video generation, and voice and music creation. Moreover, data-driven personalized message generation enables advertisers to deliver tailored experiences to consumers, thereby maximizing the effectiveness of advertising campaigns. This study analyzes the integration of Generative AI technology into commercial advertising production and proposes strategic approaches through the application of the Problem-Based Learning (PBL) methodology. By adopting this approach, advertisers can effectively address real-world challenges in their creative processes. The convergence of Generative AI and PBL methodology empowers advertisers to execute innovative ideas more efficiently and effectively, providing a critical tool for maintaining and enhancing competitiveness in a rapidly evolving digital landscape. The primary purpose of this study is to develop an educational model for video production that leverages Generative AI technology, combined with a Problem-Based Learning (PBL) approach, to verify its practical educational effectiveness. By dividing the video production process into three stages—Pre-Production, Production, and Post-Production—this study aims to propose specific methods for utilizing Generative AI at each stage, thereby helping learners cultivate both creative problem-solving skills and critical thinking abilities. This study sets the following three detailed objectives. First, it aims to analyze the impact of Generative AI technology on the video production process and propose effective educational strategies. Second, it seeks to develop an educational model focused on fostering learners' ability to independently define and solve problems through the PBL approach. Third, by validating the practical applicability of this model in educational settings, the study aims to provide future directions for video production education and contribute to the cultivation of creative and interdisciplinary talents [1].